2001
DOI: 10.1046/j.1365-294x.2001.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and levels of gene flow in Rhododendron metternichii var. hondoense revealed by microsatellite analysis

Abstract: Parentage analysis was conducted to elucidate the patterns and levels of gene flow in Rhododendron metternichii Sieb. et Zucc. var. hondoense Nakai in a 150 x 70 m quadrant in Hiroshima Prefecture, western Japan. The population of R. metternichii occurred as three subpopulations at the study site. Seventy seedlings were randomly collected from each of three 10 x 10 m plots (S1, S2, and S3) on the forest floor of each subpopulation (A1, A2, and A3). Almost all parents (93.8%) of the 70 seedlings were unambiguou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 45 publications
3
41
0
1
Order By: Relevance
“…Recent intensive field studies of populations showed that northern populations flower during the spring, whereas southern populations flower heterogeneously at different times of the year (Chi, 2009). Flowering time differences between populations have also been reported in other Rhododendron species (Kudo, 1993;Kameyama et al, 2001;Mejías et al, 2002). The occurrence of reproductive isolation or reproductive incompatibility is related to assortative mating, because immigrants that flower at different times from those of local individuals cannot reproduce, and as a consequence no gene flow occurs (Gavrilets and Vose, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Recent intensive field studies of populations showed that northern populations flower during the spring, whereas southern populations flower heterogeneously at different times of the year (Chi, 2009). Flowering time differences between populations have also been reported in other Rhododendron species (Kudo, 1993;Kameyama et al, 2001;Mejías et al, 2002). The occurrence of reproductive isolation or reproductive incompatibility is related to assortative mating, because immigrants that flower at different times from those of local individuals cannot reproduce, and as a consequence no gene flow occurs (Gavrilets and Vose, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Gene flow and spatial genetic structure in Cercidiphyllum japonicum T Sato et al not exclude any true parents (Dow and Ashley, 1996;Kameyama et al, 2001). Where there were more than two nonexcluded parents, the categorical allocation method (Marshall et al, 1998) was used to select the most likely parent from the pool of nonexcluded parents.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…Recently, highly polymorphic microsatellite markers have become a popular genetic tool in ecological studies, and have been utilized for various analyses, such as parentage analysis to identify realized contemporary gene flow (Dow and Ashley, 1996;Isagi et al, 2000;Kameyama et al, 2001;Jones and Ardren, 2003), detection of fine-scale genetic structure (Streiff et al, 1998;Ueno et al, 2000;Kameyama et al, 2002), and the analysis of amongpopulation genetic structure (Kikuchi and Isagi, 2002;Heuertz et al, 2004). In this study, we used five nuclear microsatellites for genetic analyses at different spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, revealing patterns and determinants of gene dispersal and reproductive success is fundamental to understanding the genetic aspects of natural regeneration in plant populations (Meagher and Thompson 1987). However, because of the high amount of genetic exclusion power required (Marshall et al 1998), there have been only a few attempts to study parentage of naturally established seedlings (Meagher and Thompson 1987;Dow and Ashley 1996;Schnabel et al 1998;Konuma et al 2000;Kameyama et al 2001;GonzalezMartinez et al 2002;Isagi and Kanazashi 2002;Jones 2003;Shimatani 2004). Nevertheless, these studies were unable to describe fully the reproductive patterns that led to the establishment of the seedling populations.…”
mentioning
confidence: 99%